The Male Gaze in Indonesian Teen Cinema: A Case Study of Di Bawah Umur (2020) - Ratna Asih Setyaningrum; Ivan Valentinus (Universitas Tidar, 2025)
Indonesian teen films play a significant role in shaping youth perspectives on identity, sexuality, and agency. While recent teen films such as Dua Garis Biru (2019), Yuni (2021), and Like & Share (2022) have explored progressive themes of teenage sexuality, many other Indonesian teen films continue to amplify gendered ideologies, both through their visual and narrative strategies. This paper examines Di Bawah Umur (2020) using Mulvey’s theory of the male gaze to analyze how cinematography, framing, and character representation contribute to the objectification of female characters. The findings show that although Di Bawah Umur presents itself as advocating adolescent reproductive health, it paradoxically sustains male-centric perspectives that undermine female agency. By foregrounding how patriarchal ideologies are subtly reproduced in youth-oriented cinema, this paper extends discussions in Indonesian film studies and gender representation. The result of this study offers a critical lens for scholars, educators, and filmmakers to interrogate how teen films construct gendered meanings and why such representations matter for young audiences in Indonesian society nowadays.